Translating (Metaphors) in the Age of AI: Opportunities, Challenges, and Implications for the EFL Classroom - Marija Brala Vukanovic (ELOPE, 2025)
The paper explores the use of AI translation tools in EFL classrooms, focusing on metaphor translation. We investigate the attitudes of first- and third-year English students at the University of Rijeka, Croatia, towards AI tools and evaluate three platforms: Google Translate, ChatGPT, and Glosbe, regarding their ability to accurately translate metaphors. The findings show a generally positive student disposition towards AI tools but also highlight frequent inaccuracies in AI-generated metaphor translations. We discuss the implications of these results for EFL teaching, emphasizing the potential value of error correction as a pedagogical tool. Our analysis suggests that the limitations of AI tools can serve as valuable pedagogical resources for fostering critical engagement, improving students’ understanding of culturally and contextually impregnated language, and enhancing their linguistic skills. Our findings underscore the need for an urgent and systematic integration of AI tools into classrooms.